The Evolution of the Cytochrome c6 Family of Photosynthetic Electron Transfer Proteins. (24th June 2021) - Slater, Barnaby; Kosmützky, Darius; Nisbet, R Ellen R; Howe, Christopher J
Abstract: During photosynthesis, electrons are transferred between the cytochrome b 6 f complex and photosystem I. This is carried out by the protein plastocyanin in plant chloroplasts, or by either plastocyanin or cytochrome c 6 in many cyanobacteria and eukaryotic algal species. There are three further cytochrome c 6 homologs: cytochrome c 6A in plants and green algae, and cytochromes c 6B and c 6C in cyanobacteria. The function of these proteins is unknown. Here, we present a comprehensive analysis of the evolutionary relationship between the members of the cytochrome c 6 family in photosynthetic organisms. Our phylogenetic analyses show that cytochromes c 6B and c 6C are likely to be orthologs that arose from a duplication of cytochrome c 6, but that there is no evidence for separate origins for cytochromes c 6B and c 6C . We therefore propose renaming cytochrome c 6C as cytochrome c 6B . We show that cytochrome c 6A is likely to have arisen from cytochrome c 6B rather than by an independent duplication of cytochrome c 6, and present evidence for an independent origin of a protein with some of the features of cytochrome c 6A in peridinin dinoflagellates. We conclude with a new comprehensive model of the evolution of the cytochrome c 6 family which is an integral part of understanding the function of the enigmatic cytochrome c 6 homologs.